Real-time spectral analysis using prism signal processing - Henry, M (IOP Publishing, 2019)
The Prism is a new signal processing object which provides fully recursive FIR filtering i.e. the computational load is small and fixed irrespective of filter length. The Prism also has negligible design cost. These features are attractive to the next generation of Industry 4.0 sensors requiring low cost and flexible signal processing. Recent work has demonstrated how, using a few simple design rules, a chain of six Prisms can create narrowband filters with arbitrary central frequency and bandwidth, also with low design and computational cost. In this paper this technique is extended to provide spectral analysis of data, whereby a sequence of filters is applied to a data set to provide selective frequency analysis.